First insight into extracellular vesicle-miRNA characterization in a sheep in vitro model of inflammation - Ciliberti, Maria Giovanna; Santillo, Antonella; Sevi, Agostino; Albenzio, Marzia; De Leo, Vincenzo; Ingrosso, Chiara; Catucci, Lucia; Caroprese, Mariangela (Frontiers in Veterinary Science, 2023)
The extracellular vesicles (EVs) and their microRNAs (miRNAs) cargo attracted the interest in veterinary field due to their regulatory role in a number of biological processes. The objectives of this study were i) to test two techniques of EVs isolation from sheep sheep peripheral blood mononuclear cells (PBMC) supernatant by using the ultracentrifugation (UC) and the reagent (REA) ones, and ii) to characterize the EVs-miRNAs profile after an in vitro inflammatory environment mediated by lipopolysaccharide (LPS). Sheep peripheral blood was collected and PBMCs were separated using a density gradient reagent. Subsequently, PBMCs were cultured at 37°C for 24 h (5% CO2) and the supernatants were collected to perform the EVs isolation. The presence of CD81+ extracellular vesicles marker was determined, and the purity of EVs isolated was calculated as a ratio between the number of EVs isolated and the protein concentration. Moreover, the morphological characterization revealed mainly round shaped structures with average sizes of 211 nm for EVs isolated by the UC and 99 nm for EVs by the REA method. Illumina NextSeq sequenced in single-end mode was used to characterize miRNAs profile and the differentially expressed (DE) miRNAs were analyzed using a combination of bioinformatics tools. Results revealed that REA method is reliable for EVs isolation from sheep supernatants; it was registered, indeed, an improvement of the recovery rate and the purity of EVs with the enhancement of the number and the expression levels of miRNAs characterized. The EVs isolated by the UC method after an LPS challenge showed 11 DE miRNAs, among which with 8 miRNAs were upregulated and 3 downregulated, while the REA method revealed an EVs cargo with 8 DE miRNAs upregulated, and 21 DE miRNAs downregulated. The master miRNAs regulators of the biological process were identified by using the MIRNA-mRNA network analysis, showing that among the higher representative miRNAs based on the centrality and betweenness, the miR-26a-5p could have a crucial role in the resolution of inflammation. Moreover, the identification of the let-7 miRNA family in all the EVs showed potential targeted genes that regulate the inflammation and immune responses.